2022
DOI: 10.5194/acp-22-9033-2022
|View full text |Cite
|
Sign up to set email alerts
|

Particle phase-state variability in the North Atlantic free troposphere during summertime is determined by atmospheric transport patterns and sources

Abstract: Abstract. Free tropospheric aerosol particles have important but poorly constrained climate effects due to transformations of their physicochemical properties during long-range transport. In this study, we investigate the chemical composition and provide an overview of the phase states of individual particles that have undergone long-range transport over the North Atlantic Ocean in June and July 2014, 2015, and 2017 to the Observatory of Mount Pico (OMP) in the Azores. The OMP is an ideal site for studying lon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 153 publications
0
11
0
Order By: Relevance
“…EDX analysis is considered semiquantitative for lighter elements, and contributions of C and O from the substrate are expected. 37 Previous studies have shown that elemental composition derived from EDX spectra is consistent with the composition of laboratory-generated standards and with the composition of ambient aerosols analyzed in bulk. 35,37−39 Based on the elemental percentages, we used k-means clustering 40 to classify each particle as one of five types: sodium-rich salt (Na-rich salt, Na ≥ 1%, and Na > K and Na > P), potassium-rich salt (K-rich salt, K > Na, K > P, and K ≥ 5%), phosphorus-rich salt (P-rich salt, P > Na, P > K, and P ≥ 1%), carbonaceous (CNO, C + N + O ≥ 97% and Na < 1%), or mixed salt for those that did not fit into one of the previously listed categories (Table S1).…”
Section: ■ Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…EDX analysis is considered semiquantitative for lighter elements, and contributions of C and O from the substrate are expected. 37 Previous studies have shown that elemental composition derived from EDX spectra is consistent with the composition of laboratory-generated standards and with the composition of ambient aerosols analyzed in bulk. 35,37−39 Based on the elemental percentages, we used k-means clustering 40 to classify each particle as one of five types: sodium-rich salt (Na-rich salt, Na ≥ 1%, and Na > K and Na > P), potassium-rich salt (K-rich salt, K > Na, K > P, and K ≥ 5%), phosphorus-rich salt (P-rich salt, P > Na, P > K, and P ≥ 1%), carbonaceous (CNO, C + N + O ≥ 97% and Na < 1%), or mixed salt for those that did not fit into one of the previously listed categories (Table S1).…”
Section: ■ Introductionmentioning
confidence: 59%
“…The particles were dominated by C (90% averaged across all samples) and contained a substantial amount of O (5%), Na (2%), and Cl (2%). The percentages for C, N, and O should be considered semiquantitative, due to limitations of the method . The respiratory particle samples contained small amounts of N, Mg, Al, Si, P, S, K, Ca, Mn, Fe, and Zn, each of which accounted for less than 1% of the particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(e) and (f) PM10 samples. Note that the categorization based on elemental compositions was slightly different for selected impinger (Cheng et al, 2022) and PM10 (Hiranuma et al, 2013) samples. The group C+N (CNO) include particles containing only carbon and nitrogen (and oxygen), mainly representative of (oxygenated) carbonaceous particles.…”
Section: Time Seriesmentioning
confidence: 99%
“…One potential explanation is that these particles might be in a liquid state with low viscosity so that they spread out and deform to a at shape when they impact the substrate. 55,91,92 Another explanation is that large particles could bounce from higher to lower stages. 89 carbonaceous particles are different, suggesting different atmospheric processing along the vertical column.…”
Section: Papermentioning
confidence: 99%